Association between dynapenic obesity phenotypes and physical performance in middle-age and older women living in community - Arteaga-Pazmiño, Cecilia; Fonseca-Pérez, Diana; Balladares Mazzini, Manuel; Galvez-Celi, Javier; Emén Sánchez, Janet; Álvarez-Córdova, Ludwig (Frontiers in Nutrition, 2024)
Background Dynapenic obesity (DO) is the coexistence of excess adipose tissue/body weight and low muscle strength. This condition is associated with an increased risk of suffering from various chronic diseases and physical deterioration in older people. Aim To analyze the association between DO phenotypes and physical performance in middle-aged women living in the community. Methods This cross-sectional study was conducted on middle-aged and older women (≥50 years) residing in Guayaquil, Ecuador. Dynapenia was diagnosticated by a handgrip strength (HGS) < 16 kg; obesity was determined based on body mass index (BMI) ≥ 30 kg/m2. Participants were categorized into four groups based on their dynapenia and obesity status: non-dynapenic/non-obesity (ND/NO), obesity/non-dynapenic (O/ND), dynapenic/non-obesity (D/NO) and dynapenic/obesity (D/O). Physical performance was assessed by the Short Physical Performance Battery (SPPB). Results A total of 171 women were assessed. The median (IQR) age of the sample was 72.0 (17.0) years. Obesity and dynapenia were 35% (n = 60) and 57.8% (n = 99) of the participants, respectively. The prevalence of ND/NO was 25.1% (n = 43), O/ND 17% (n = 29), D/NO 39.8% (n = 68) and DO 18.1% (n = 31). The mean SPPB total score was 6.5 ± 3.2. Participants of D/NO and DO groups presented significantly lower mean SPPB scores (p < 0.001) compared to those of NO/ND and O/ND groups. Conclusion Women with DO and D/NO exhibited significantly lower SPPB scores, indicating poorer physical performance. These findings emphasize the importance of incorporating a comprehensive assessment of muscle strength and obesity in middle-aged and older women.